ENGINEERING PEDAGOGY AS A BASE FOR TECHNICAL TEACHER TRAINING SYSTEM - V. V. KONDRATYEV (Moscow Polytechnic University, 2018)
Engineering pedagogy as a science could be considered in different aspects and from several sides: as a scientific discipline, as an educational module in higher school structure, as an ideology for technical teacher's activities. The author asserts that pedagogy is a methodologically fundamental system featuring a specific interrelation between the components of natural sciences, Humanities and applied knowledge on the basis of logic of engineering activities. The major difference of engineering pedagogy is in its aims and values. It sets competences of engineering activity as its aims and values. The paper marks out the leading areas of integration of different types of knowledge, formulates the definitions of an object, subject and research problems of engineering pedagogy. Its major categories and their functions are viewed. The author argues that engineering pedagogy is concurrently a fundamental and applied science as its categories and concepts have a scientific status and may serve as a methodological basis for training engineering personnel. One of its main features is interdisciplinarity which is used for solving concrete problems. Interdisciplinarity is viewed as a modern form of fundamentality and a vector of university education modernization. In conclusion the author formulates the conceptual provisions for designing technical teacher training system.